Developing Inter-faith Tolerance in Indonesia: A Literature Study on Challenges and Supporting Factors - Kirana, Teresa Amarita Maia (International Journal of Religion Education and Law, 2026)
Indonesia, as a multicultural country with religious diversity, considers tolerance essential for maintaining social harmony. This literature study aims to analyze the phenomenon of religious intolerance in Indonesia, identify its root causes, and examine the challenges and key factors that support efforts to build religious tolerance. Based on a literature synthesis, it was concluded that despite legal guaranties, intolerance is still prevalent, driven by exclusivist views, fanaticism, a lack of inclusive religious understanding, the role of social media, and religious education curricula that are not yet comprehensive. Several factors supporting efforts to build tolerance include the role of education, the role of community, and the role of family.